A novel agent targeting APRIL: A new hope for elderly patients of IgA nephropathy - Xin Liu; Li Zuo (Aging Medicine, 2025)
Sibeprenlimab is a humanized IgG2 monoclonal antibody that binds to and neutralizes the activity of APRIL. It should usher in a new era in the treatment of IgAN, especially in elderly patients.